The effect of PEG functionalization on the in vivo behavior and toxicity of CdTe quantum dots. Issue 22 (17th April 2019) - Du, Yan; Zhong, Yuanyuan; Dong, Jingjing; Qian, Chuntong; Sun, Shian; Gao, Liping; Yang, Dongzhi
Abstract : CdTe quantum dots (QDs) are considered a potential toxic substance because they contain metal ions. Abstract : CdTe quantum dots (QDs) are considered a potential toxic substance because they contain metal ions. However, most toxicology data are derived from in vitro studies or limited in vivo analysis and may not reflect in vivo responses and biodistribution. Proper modification is one of the most widely used routes to reduce the toxicity of QDs. Herein, we demonstrated the role of polyethylene glycol (PEG) in decreasing the toxicity of QDs by studying the animal survival, clinical biochemistry, organ histology, biodistribution and oxidative stress in thioglycolic acid (TGA)- and mercapto-acetohydrazide (TGH)-stabilized CdTe QD (TGA/TGH-CdTe QD)-treated groups. Via the histology, transmission electron microscopy (TEM) and biodistribution results, it was found that the QDs mainly accumulated in the liver and kidney at 7 days post-injection, and obvious tissue damage was also observed in the bare TGA/TGH-CdTe QD group. Based on the evaluation of oxidative stress in the liver and kidney, the indicators exhibited an obvious variation with a high dose of TGA/TGH-CdTe QDs. In contrast, the QD aggregation decreased in the liver and kidney with no clear physiological index variation after PEG functionalization. Thus, PEG plays an important role in decreasing the toxicity of the CdTe QDs, and both the accumulation of cadmium and oxidative stress variation instead of an isolation factor are responsible for the in vivo toxicity of these QDs.